PENGARUH KUALITAS PELAYANAN DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH KOPERASI SIMPAN PINJAM SEHATI MAKMUR ABADI CABANG MATARAM - Rido, Muhammad; Annisa (Universitas Islam Negeri Mataram, 2023)
This study aims to determine the effect of service quality and customer value on customer satisfaction in using savings and loan services at KSP Sehati Makmur Abadi, Mataram branch. The population of this study are customers who are members of KSP Sehati in Mataram City. The research method used is quantitative associative with primary data types. The sampling technique used simple random sampling with a total sample of 100 customers who were determined using the Slovin formula and data collection using a questionnaire (questionnaire). While the analysis techniques used in this research are research instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The research results obtained using the IBM SPSS version 26 application show that: (1) Partially service quality (X1) has a significant effect on customer satisfaction (Y) using savings and loan services at KSP Sehati Makmur Abadi Mataram Branch. (2) Partially, customer value (X2) has a significant effect on customer satisfaction (Y) using savings and loan services at KSP Sehati Makmur Abadi Mataram Branch. (3) Simultaneously service quality (X1) and customer value (X2) have a significant effect on customer satisfaction (Y) in using savings and loan services at KSP Sehati Makmur Abadi Mataram Branch.